Inflammatory Bowel Disease [IBD] and Physical Activity: A Study on the Impact of Diagnosis on the Level of Exercise Amongst Patients With IBD. (18th December 2018) - Gatt, K; Schembri, J; Katsanos, K H; Christodoulou, D; Karmiris, K; Kopylov, U; Pontas, C; Koutroubakis, I E; Foteinogiannopoulou, K; Fabian, A; Molnar, T; Zammit, D; et al.
Abstract: Background and Aims: Inflammatory bowel disease [IBD] can impair patients' functional capacity with significant negative effects on their quality of life. Our aim was to determine the impact of IBD diagnosis on fitness levels and to assess the levels of engagement in physical activity and fatigue in IBD patient before and after diagnosis. Methods: A prospective multi-centre cross-sectional study was performed. Patients diagnosed with IBD in the previous 18 months were recruited. Inclusion criteria included clinical remission and/or no treatment changes within the previous 6 months. Physical exercise levels were assessed by the Godin score and fatigue levels was assessed by the functional assessment of chronic illness therapy [FACIT] score. Results: In total, 158 patients (100 Crohn's disease [CD]) were recruited. Mean age was 35.1 years (95% confidence interval [CI] ± 2.0). Gender distribution was approximately equal [51.3% male]. The Mean Harvey Bradshaw and Simple Clinical Colitis Activity indices were 2.25 [95% CI ± 0.40] and 1.64 [95% CI ± 0.49], respectively. The mean Godin score difference before and after IBD diagnosis was 6.94 [ p = 0.002]. Patients with ulcerative colitis [UC] [41.8%] were more likely than patients with CD [23.0%] to reduce their exercise levels [ p = 0.04]. FACIT scores were lower in patients who had experienced relapses [ p = 0.012] and had severe disease [ p = 0.011]. Approximately one-third of patients reduced their activity level following IBD diagnosis. Conclusions: Patients were significantly less physically active after a diagnosis of IBD and this was more apparent in UC. Identification of the risk factors associated with loss of fitness levels would help to address the reduced patient quality of life.